A retrospective pharmacovigilance study of antiretroviral therapy in a pediatric setting in benin - ALLABI, AUREL CONSTANT EUSTACHE; Gratien, Sagbo; Ekanmian, Giraud; Koumakpai-Adeoty, Sikiratou; Ganfon, Habib; Ganfon, Habib; Sarfo, Maame Anima A- (My University, 2017)
Objective: With the new WHO recommendations, the new eligibility criteria for antiretroviral therapy suggest an early start of treatment which causes a longer duration of exposure to antiretroviral therapy especially for children and newborns. It therefore appears essential due to the potential risks associated with the use of antiretroviral drugs, to promote the care of patients by looking out for adverse drug reactions to improve the safety of the treatment. Methods: We conducted a Pharmacovigilance retrospective study from January 2002 to July 2013. It included 237 HIV positive children on Antiretroviral Therapy (ART) who were monitored on the pediatric ward of the teaching hospital CNHU-HKM of Cotonou in Benin Republic. Results: Adverse events (AEs) accounted for 8.7% of the reason for change in ARV treatment and this was mainly due to the tri-therapy lamivudine + zidovudine + (nelfinavir or nevirapine) which was responsible for 62.5% of all cases. Most common AEs affected the skin and the digestive system: pruritus (28.89%), diarrhea (13.33%), and skin outbreak (11.11%). The incidence of AEs for the various combinations: lamivudine + zidovudine + efavirenz, lamivudine + zidovudine + nevirapine, lamivudine + stavudine + nevirapine and lamivudine + zidovudine + nelfinavir, were respectively 2.55, 3.19, 4.77 and11.54 cases for 1000 persons-month. Serious AEs accounted for11.11% of the cases and this was related to anemia and this was linked to the combination lamivudine + zidovudine + nelfinavir, and this was responsible for 4.4% cases of hospitalization. Serious AEs also included bone deformation imputed to lamivudine + zidovudine + nelfinavir and lamivudine + stavudine + nelfinavir and amyotrophy imputed to lamivudine + didanosine + nelfinavir. The mechanism of occurrence of the AEs was more pharmacological (47%) often with the combination oflamivudine +zidovudine + nelfinavir than immuno-allergic (44%) or chronic (9%). The average onset of adverse event was 9 months. Advanced age and serious immunological deficiency at the beginning of the tri-therapy and a concomitant antitubercular treatment as well as the seronegative status of the tutor favored the appearance of the AEs. Conclusion: Our results show that it is better to start early ART in order to reduce the occurrence of Adverse Drug Reactions. Active Pharmacovigilance should be implemented in pediatric settings in order to optimize the therapeutic monitoring of patients and prevent the occurrence of adverse drug reactions.
Keywords: Antiretroviral Therapy; Adverse Events; Children Pharmacovigilance